Effects of Type and Strength of Force Feedback on Movement Time in a Target Selection Task. (September 2013) - Rorie, R. Conrad; Vu, Kim-Phuong L.; Marayong, Panadda; Robles, Jose; Strybel, Thomas Z.; Battiste, Vernol
Future cockpits will likely include new onboard technologies, such as cockpit displays of traffic information, to help support future flight deck roles and responsibilities. These new technologies may benefit from multimodal feedback to aid pilot information processing. The current study investigated the effects of multiple levels of force feedback on operator performance in an aviation task. Participants were presented with two different types of force feedback (gravitational and spring force feedback) for a discrete targeting task, with multiple levels of gain examined for each force feedback type. Approach time and time in target were recorded. Results suggested that the two highest levels of gravitational force significantly reduced approach times relative to the lowest level of gravitational force. Spring force level only affected time in target.